Թուրքական արխիվներում Հայոց ցեղասպանությանը վերաբերող վավերագրերի գոյության հարցի շուրջ - Մուրադյան, Սամվել («Զանգակ - 97»)
Scientific and official-political publications in Turkey often State that the country's archives are open to any researcher and that there are no records of а Genocide whatsoever. A careful study of relevant sources and spccialized literature demonstrates clearly that, starting from 1918, public establishments in Turkey carried out consistcnl work for ex-patriation and removal from archives with subsequent elimination of any documentation, court-dcposited evidences, official Orders and reports regarding the massacres and deportations of Armenians.
Keywords: Հայոց պատմություն; Հայոց ցեղասպանություն